Perceptions of students on a stand‐alone dental materials course in a revised dental curriculum. (3rd September 2020) - Soni, Vishani; Kotsane, Daisy F; Moeno, Sharon; Molepo, Julitha
Abstract: Background: The Dental Materials (DM) course was introduced as a stand‐alone course in 2013, at the University. Prior to that, DM was integrated into clinical courses. Objective: To determine the perceptions of the Bachelor of Dental Science (BDS2 to BDS5) students on a stand‐alone DM course following curricular amendment. Methods: This was a cross‐sectional study, in which a simple random sampling strategy was used, with forty‐six students participating. The study was conducted in 2017. A self‐administered, structured, validated questionnaire was used to collect data. The obtained data were summarised and analysed using descriptive and inferential statistics (one‐way ANOVA). Results: The study was conducted on Bachelor of Dental Science (BDS2 to BDS5) students. A response rate of 49% from the administered questionnaires was achieved. The overall perception, total mean percentage score of 71.4% was obtained showing a generally positive view on the relevance of the course by students. A total mean percentage score of 74.1% showed the students' view that the DM course was well managed whilst a total mean score of 56.7% expressed the overall view on the reintegration of DM into clinical courses. Conclusion: The students felt that DM was relevant and it could continue as a stand‐alone course. They perceived that the course was run effectively and managed well, but they had conflicting views on reintegration of the course into clinical modules. Studies with larger sample sizes at other Dental Schools are recommended to determine similarity of results.